Influence of top management commitment, stakeholder pressure and public concern on sustainable environmental manufacturing practices in Malaysia: Data screening and preliminary analysis - Olusegun, Adebambo Hameed; Ashari, Hasbullah; Nordin, Norani (Globeedu Group, 2014)
This research paper explored the screening procedures and preliminary analysis of the data collected regarding the influence of top management commitment, stakeholder pressure and public concern on sustainable environmental manufacturing practices in the Malaysian manufacturing industry.One hundred and three companies from different Malaysian manufacturing industry completed the mail-administered questionnaire on a 6-point Likert scale.The collected data was analysed by using Statistical Package for Social Sciences (SPSS) application software version 20.Towards the achievement of the satisfaction of the assumptions of multivariate analysis, data screening and preliminary analysis was performed.Precisely, the missing values, outliers, normality and multicollinearity test were conducted and the results show that the data were fit and qualified for further use in the multivariate analysis.